ALEGORIS TOKOH DALAM NOVEL RAFILUS KARYA BUDI DARMA: ANALISIS SEMIOTIKA C.S. PIERCE - Martawati; Andi Tenri Sua; Irna Fitriana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to identify the forms of allegorical signs in characters in the novel Rafilus by Budi Darma using a semiotic approach proposed by Charles Sanders Peirce. This research employs a qualitative method with a descriptive design. Data were collected through literature review, note-taking, and reflective-introspective techniques, while data validity was ensured through triangulation. The data analysis applied the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The results reveal that the forms of allegorical signs in the novel Rafilus are represented through five main characters: Rafilus, Jumarup, Van der Kloning, Pawestri, and Munandir. These characters are constructed as semiotic representations encompassing icons, indexes, and symbols. Iconic signs are reflected in the resemblance between the characters’ traits, conditions, or events and certain realities. Indexical signs emerge through causal relationships between the characters’ experiences and the meanings produced. Meanwhile, symbolic signs are indicated by the association between characters and socially and culturally constructed conventions. Thus, the use of allegorical signs in the characters functions not merely as a narrative element but also as a system of signs that constructs complex meanings. These three forms of signs collectively position the characters as allegorical entities representing human realities in social, moral, and existential dimensions.